(untitled) (American Journal of Islam and Society, 1985)
The members of the editorial staff of the AJISS were very encouraged by the response from readers after the release of Volume 2, Number 1 of the journal. Apparently many readers were impressed by the new name and the new format. Some readers see the new name of the journal as a challenge to Muslim social scientists to take a stand on important human issues and to conduct their research and analyses within an Islamic framework. One reader reminded me of an article written by James M. Gustafson on “Man In Light of Social Science and the Christian Faith.” Apparently this Christian author was concerned about some of the same philosophical and epistemological issues that stir us in this journal. This is to say, as a Christian thinker, Gustafson claims the right “to interpret man from the Christian perspective as well, and. . .sees things in this light that the lights from the social science do not expose.” Regardless of how some of the social scientists in the academic community view statements like that of Gustafson’s, the fact remains that those who believe in a sublunar world (Dunya) and a transcendenA world (al-Akhira) will always adopt critically the methods and research findings of the secular social science. In this volume we have a number of interesting and infromative articles that raise a host of issues about the Islamic experience. The lead article is written by Roger Garaudy, a French Muslim who takes a critical look at the Western philosophical tradition from the perspective of a Muslim student of human knowledge. His analysis is a part of the beginning of Western Muslim attempts to probe deeply into their own intellectual tradition in light of their understanding of their Muslim intellectual heritage. Following Garaudy’s paper are several other papers dealing with Ibn Hazem, Amir Ali, Ibn Khaldun and Mawlana Mawdudi. The Ibn Hem’s piece treats us to a careful analysis thinker’s thought on Qiyas in Islamic law; Amir Ali’s article addresses the Muslim thinkers views of Islam early in this century; the Ibn Khaldun essay gives us an alaysis of the North African Muslim’s under.,tanding of perception theories of his time; the Mawdudi piece treats us to a careful analysis of the Pakistani Muslim writer’s tafsir of the Holy Qur’an. The article of Z.I. Ansari provides an analysis of the life and activities of Imam Mrith Deen Muhammad, the successor of the late Honorable Elijah Muhammad and one of the leading MusIim figures in America today ...